MELACAK AKAR IDEOLOGI PURITANISME ISLAM: SURVEI BIOGRAFI ATAS “TIGA ABDULLAH” - Jinan, Mutohharun (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2014)
This paper examined the variant of Islamic movement with biographical point of view to three muslims figures, namely Abdullah Sungkar (the founder of Jemaah Islamiyah), Abdullah Marzuki (the founder of Majelis Pengajian Islam), and Abdullah Thufail Saputro (the founder of Majelis Tafsir Al-Qur’an). They have been known as the “Triple A”. They have been being very influential in the dynamics of Islam in Surakarta since the 1970s until today. They have worked together to spread the teachings of Islam in many religious activities. Applying qualitative approach and using documentation study, it was founded that due to many differences in intellectual backgrounds and ideological orientations of each other that lead them to choose different strategies to realize the ideal Islamic society. The first figure selected resistant position and fight against the hegemony of the state, the second figure chose neutral and do not care about political issues, and the third figure to choose the path of accommodative policy of the state.***Artikel ini membahas tentang varian gerakan Islam di Surakarta dengan pendekatan biografi tokoh. Tokoh yang dijadikan objek kajian adalah Abdullah Sungkar (pendiri gerakan Jamaah Islamiyah), Abdullah Marzuki (pendiri Majelis Pengajian Islam), dan Abdullah Thufail Saputro (pendiri gerakan Majelis Tafsir Al-Quran). Tiga tokoh ini dikenal oleh masyarakat dengan sebutan Tiga A. Pemikiran dan lembaga mereka sangat berpengaruh dalam dinamika perkembangan dan dakwah Islam di Surakarta pada tahun 1970-an hingga sekarang. Mereka pernah bekerja sama dalam lembaga dakwah. Dengan pendekatan kualitatif dan kajian dokumen ditemukan bahwa karenas beberapa perbedaan latar belakang, pandangan, dan orientasi ideologi menjadikan mereka berpisah dan membentuk gerakan sendiri-sendiri. Abdullah Sungkar memilih jalur berseberangan dengan negara, Abdullah Marzuki memilih jalur pendidikan pesantren dan tidak berpolitik, sedangkan Abdullah Thufail Saputro memilih jalur akomodasi dan bekerjasama dengan negara.